Optical variability of NGC 4151 during past 100 years - Chuvaev, K.K.; Oknyanskij, V.L.; Lyuty, V.M. (Известия Крымской астрофизической обсерватории, 2008)
We present historical optical light curve of NGC 4151 over 1906–2007 based on our photographic and photoelectric data as well as other published photometrical data reduced to the same system. We have found quasi-periodic component about 15.6 years in the 100-year light curve and that is close to our old result. We present results of optical spectrophotometry during 1972–1991 using the monitoring data of K.K. Chuvaev. We have performed the cross-correlation analysis to find out time delays between continuum and line variations.